Description and distribution of genus Dieffenbachia associated to banana plantations in Costa Rica. - Brenes-Prendas, Steven; Agüero-Alvarado, Renán (Agronomía Mesoamericana, 2012)
Description and distribution of genus Dieffenbachia associated to banana plantations in Costa Rica. Twenty three banana farms were sampled between 2006 and 2009 for Dieffenbachia species. Field samples were taken to thelaboratory for identifi cation. Field distribution and frequency were recorded and the frequency – cover index (IFC) was obtained for each species. Three species associated to banana plantations were found, Dieffenbachia oerstedii,Dieffenbachia tonduzii and Dieffenbachia concinna; besides,a potential hybrid from D. oerstedii and D. tonduzii was observed. D. oerstedii showed the highest IFC (40,8%),followed by D. tonduzii (8,2%) and D. concinna (0,5%).Currently, D. oerstedii appears as the dominant speciesof this genus in banana plantations in the agroecosystems evaluated.